Suburethral Slingplasty Using a Self-fashioned Gynemesh for Treating Urinary Incontinence and Anterior Vaginal Wall Prolapse - Chi-Feng Su; Soo-Cheen Ng; Kwong-Pang Tsui; Gin-Den Chen; Horng-Jyh Tsai (Elsevier, 2009)
Objective: This study was conducted to evaluate the effectiveness of self-fashioned Gynemesh for the concomitant treatment of urinary incontinence and anterior vaginal wall prolapse, and the factors involved in mesh erosion. Materials and Methods: From March 2004 to September 2006, 65 women with urinary incontinence, with or without pelvic organ prolapse or prior surgery for prolapse or incontinence, were recruited for this study. A self-fashioned Gynemesh was used for the concomitant treatment of urinary incontinence and anterior vaginal wall prolapse. Patients in this study underwent suburethral slingplasty and/or concomitant pelvic reconstructive operations. A general linear model univariate analysis was performed to assess the relationships between mesh erosion and various variables. Results: The mean postoperative follow-up was 33 months. Those patients with anterior wall prolapse presented as completely cured postoperatively. The cure rate for urinary incontinence was 80%, and the improvement rate was 17%. Vaginal mesh erosion was discovered in four patients (6%) during the postoperative follow-up. These four patients remained continent after the removal of the eroded mesh. The interactive effects for mesh erosion by a general linear model analysis were menopausal women with advanced anterior vaginal wall prolapse (p < 0.05) and women with advanced anterior vaginal wall prolapse with concomitant sacrospinous ligament fixation (p < 0.05). Conclusion: We found that using self-fashioned Gynemesh for tension-free suburethral and anterior vaginal slingplasty provided a high success rate (97%) in the 3 years of follow-up. Mechanical rejection may be one of the causes of vaginal mesh erosion.